Ambivalence on the front lines? Attitudes toward Title IX and women's sports among Division I sports information directors. (February 2014) - Hardin, Marie; Whiteside, Erin; Ash, Erin
In light of continuing research that assesses how dominant ideology is communicated via mediated sport, this study examines the attitudes of sports information directors (SIDs), arguably initial "gatekeepers" in the media production process and, thus, critical players in shaping sports media messages. A random sample of Division I SIDs was surveyed on questions clustered around gender and sexuality issues. The results showed that Division I SIDs are likely to help gay athletes stay in the closet, although they express more progressive attitudes toward sexuality than sports journalists, who were similarly surveyed in 2009. The results also showed mixed support for women's sports and Title IX – with implications for coverage – and strong support for a gendered division of labor that could be problematic for the future prospects of women in the profession. The authors use the survey to question assumptions that female SIDs will advocate on behalf of women's sports, Title IX and other related issues.